The macroeconomic effects of the Euro Area's fiscal consolidation 2011-2013: A simulation-based approach - Ansgar Rannenberg; Christian Schoder; Jan Stráský (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2015)
We simulate the Euro Area's fiscal consolidation between 2011 and 2013 by employing two DSGE models used by the ECB and the European Commission, respectively. The cumulative multiplier amounts to 0.7 and 1.0 in the baseline, but increases to 1.3 with a reasonably calibrated financial accelerator and a crisis-related increase of the share of liquidity constrained households. In the latter scenario, fiscal consolidation would be largely responsible for the decline in the output gap from 2011-2013. Postponing the fiscal consolidation to a period of unconstrained monetary policy (until after the economic recovery) would have avoided most of these losses. – – Wir simulieren die Haushaltskonsolidierung im Euroraum im Zeitraum 2011 bis 2013 mit Hilfe von zwei DSGE Modellen der EZB und der Europäischen Kommission. Der kumulative Multiplikator beträgt 0.7 bzw. 1.0 in der Basislinie, steigt aber auf 1.3, wenn die Modelle um einen plausibel kalibrierter Finanzakzelerator erweitert und der Anteil liquiditätsbeschränkter Haushalte krisenbedingt erhöht wird. Im letzteren Szenario trägt die Haushaltskonsolidierung die maßgebliche Verantwortung für die Verschlechterung der Produktionslücke im Zeitraum 2011 bis 2013. Wäre die Haushaltskonsolidierung erst in einer Phase mit uneingeschränktem geldpolitischen Handlungsspielraum vorgenommen worden (d.h. nach der Erholung der Wirtschaft) hätte der Großteil der BIP-Verluste verhindert werden können.
urn:nbn:de:101:1-201602195021
Keywords: E32; E62; 330; fiscal policy simulations; fiscal consolidation; fiscal multiplier; Euro Area